2008
DOI: 10.1007/s10495-008-0214-9
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis

Abstract: The objective of this study was to evaluate the cardiac toxicity induced by carboplatin, a second generation platinum-containing anti-cancer drug, and to test whether pravastatin can reduce this cardio-toxicity. In the present study, infusion of carboplatin (100 mg/kg) to mice resulted in decreased survival rates and abnormal cardiac histology, concomitant with increased cardiac apoptosis. In addition, treatment of cultured rat cardiomyocytes with carboplatin (100 muM for 48 h) caused marked apoptosis and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Cholesterol-independent effects of statins include indirect anti-inflammatory effects such as activation of reduction-oxidation reaction-sensitive transcription factors (Gueler et al, 2002). Statins also protect tissues from various types of insults such as ischemia-reperfusion injury in the kidney and heart (Li et al, 2004b;Birnbaum et al, 2005;Gueler et al, 2007;Cheng et al, 2008).…”
mentioning
confidence: 99%
“…Cholesterol-independent effects of statins include indirect anti-inflammatory effects such as activation of reduction-oxidation reaction-sensitive transcription factors (Gueler et al, 2002). Statins also protect tissues from various types of insults such as ischemia-reperfusion injury in the kidney and heart (Li et al, 2004b;Birnbaum et al, 2005;Gueler et al, 2007;Cheng et al, 2008).…”
mentioning
confidence: 99%
“…Thus, additional exogenous ROS, either caused by ROS-generating agents or anti-oxidant inhibitors, are likely to trigger more ROS damage in cancer cells (10,33). The conventional chemotherapeutic drugs used in the present study have been shown to increase ROS production in cancer cells (25)(26)(27)(28)(29)(30). Additionally, safingol has been demonstrated to generate ROS in fungi and plant cells (18,19).…”
Section: Discussionmentioning
confidence: 93%
“…The conventional chemotherapeutics to be combined with safingol, i.e., carboplatin, doxorubicin, gemcitabine and vincristine, were selected based on their ability to generate ROS (25)(26)(27)(28)(29)(30). Examination of the treatment outcomes of various safingol-based combination regimens was performed based on the application of the combination index (CI) developed by Chou and Talalay, which allows quantitative representation of the potential synergism between safingol and the conventional chemotherapeutic agents (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, a big limitation of chemotherapy is its nonspecific toxicity to normal cells during general administration against tumor cells. Many studies have demonstrated that multiple chemotherapy reagents damage normal cells through oxidative stress, for example, doxorubicin is well known for causing oxidative stress-induced cardio and neural toxicity (1); Carboplatin, another widely used chemotherapy compound, has been reported to induce oxidative stress-related ototoxicity in the inferior colliculus (2,3). Therefore, it is critical to search for strategies to selectively reduce normal cell toxicity while preserving efficacy of chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%